Integrasi Pendidikan Anti Narkoba dalam Pendidikan Agama Islam dan Budi Pekerti Kurikulum 2013 - Machali, Imam (NADWA, 2014)
This article describe the antidrug education and the integration of anti-drug education in the curriculum of Islamic religious and moral education of the year 2013. The results showed that the antidrug education began in elementary, jun-ior and senior high school that includes knowledge about drugs and the dangers, increase self-esteem, and the formation of assertiveness. Integration of anti-drug education in the curriculum of Islamic religious education and moral includes three aspects, namely: knowledge (cognitive), attitudes and behaviours (affec-tive), and skills (psychomotor). Implementation of antidrug education at school level using integrative-inclusive strategy. Anti-drug education learning man-agement can be integrated in all subjects, both religious and secular.Keyword: antidrug education, curriculum 2013